Cook simply, live fully : flexible, flavorful recipes for any mood - Fahr, Yasmin (Harper, an imprint of HarperCollins Publishers, 2024)
What's for dinner? It's a question we ask ourselves most nights -- pressed for time or groceries, searching through the fridge for inspiration. Dinner can be a time to unwind and connect with family or friends, but it can also feel like a chore. Recipe developer and cookbook author Yasmin Fahr gets it, and is here to help readers creature nourishing meals even when real life seems to have other plans. In Cook Simply, Live Fully she offers 120 recipes for taking the grind out of dinnertime, with dishes that span the range of "too tired to chop vegetables" to "up for a challenge but please make it snappy." Yasmin's approach is all about simplicity and flavor while keeping things nutritious and vegetable-forward. Organized into three progressive sections based on energy level and mood: Lap Dinners include low effort/high reward meals, Coffee Table Dinners take things up a notch with satisfying dishes that require a little more prep work, and At the Dinner Table is for those days when time and energy are not at a premium, or when entertaining is on the menu. Yasmin's recipes are designed to teach readers how to become better, more intuitive cooks, and are open to creative substitutions (and some trial and error). Throughout, she shows readers how to transform the familiar by creating new pairings and flavor combinations that will inspire endless iterations -- all while keeping prep and cleanup time to a minimum. An inviting, beautifully styled cookbook featuring 75 full-color photographs, Cook Simply, Live Fully is the answer to the most difficult question home cooks face every day, and is sure to become a trusted resource for years to come.